Lesbiandades: o ruído das mídias constrói desinformação - Lira, Flávia Blanco (2019)
The present research stems from a concern regarding representations of lesbian women in our cultural imaginary in narratives conveyed by the media, both digitally and in print, and also in audiovisual, literary and artistic productions. The hypothesis is that the establishment of this imaginary in these various spheres produces discourses which go in the opposite direction of the current feminist struggles. The aim was to demonstrate how, despite of what we might believe, those stories and the terms, words and images employed in them, are perpetuating chauvinistic, misogynistic, and heteronormative ideas, reinforcing invisibility of feminine and lesbian‟s issues. The examples constituting the corpus of this investigation have been analyzed through a theoretical foundation based on the following bibliography: Judith Butler (2003, 2015 and 2016), Simone de Beauvoir (2016), Adrienne Rich (2012), Djamila Ribeiro (2017), bell hooks (2019), Liv Strӧmquist (2018), Audre Lorde (2013) and Virginie Despentes (2016). The methodology used was firstly a bibliographical review of those aforementioned thinkers about feminism, gender and sexuality, place of speech, lesbian existences, compulsory heterosexuality and diversity, in order to understand, under a lesbian-feminist look and speech, how this imaginary interferes in cultural and social relations. It is urgent to contribute to the disclosure of broadening narratives with information, instead of prejudice, on the reflection about gender issues in our country. This dissertation was built as an alternative approach in order to collaborate with the imperative of deflating hate speeches that have been increasing lately, reinforcing damaging invisibilities